Ab initio Study of New Phosphino PCP Pincer Ligand, C6H4-1-(CH2PPh2)-3-(CH(CH3)PPh2) - NAGHIPOOR, ALI; HAJI GHASEMI, ZAHRA; ABBASI, SHAHRYAR (Asian Journal of Chemistry, 2010)
Multidentate ligand systems, both cyclic and acyclic can be designed to bind transition metals in a predictable manner. The steric constraints of such ligands and the nature of the donor atoms determine to a large extent the stability and properties of the metal complexes. Here in, the new PCP pincer ligand, C6H4-1-(CH2PPh2)-3-(CH(CH3)PPh2), has been theoretically studied by ab initio restricted Hartree-Fock (RHF).